Cavendish Banana Peel Extract's Antibacterial Activities Potential as Disinfectant - Ramadhan, Erlangga Lazuardi; Retnowati, Wiwin; Dewanti, Linda; Wahyunitisari, Manik Retno (Universitas Airlangga, 2023)
Highlights:1. The COVID-19 pandemic makes personal hygiene more important than ever, and antibacterial substances such as disinfectants are crucial in maintaining said hygiene.2. The MBC of cavendish banana peel extract against the growth of bacteria Escherichia coli and Staphylococcus aureus was 25%, with no activity against Bacillus subtilis.3. Musa acuminata peel extract has the potential to be used as a disinfectant. AbstractIntroduction: The COVID-19 pandemic makes personal hygiene more important than ever, and antibacterial substances such as disinfectants are crucial in maintaining said hygiene. This study aimed to determine the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of cavendish banana peel extract (Musa acuminata) against Staphylococcus aureus, Escherichia coli, and Bacillus subtilis. Methods: The design of this study was a laboratory experiment that used the broth dilution method with test tubes using methanol as the extract's solvent. Sterile aquadest was used as the solvent, and Mueller-Hinton broth was used as the growth medium in tubes. All samples of the bacteria (Staphylococcus aureus, Escherichia coli, and Bacillus subtilis) were provided by the Laboratory of Microbiology Faculty of Medicine, Universitas Airlangga.Results: MBC was the only parameter found due to the color and particulates, which hindered the turbidity assessment of MIC. From the dilution test, the MBC of cavendish banana peel extract against the growth of bacteria Escherichia coli and Staphylococcus aureus was 25%, with no activity against Bacillus subtilis.Conclusion: There were antibacterial activities of Musa acuminata peel extract against Staphylococcus aureus and Escherichia coli. Therefore, it has the potential to be used as a disinfectant.